Pengaruh Terapi Pijat Bayi Terhadap Peningkatan Berat Badan dan Kualitas Tidur Pada Bayi Umur 6-12 Bulan di TPMB Ika Natalia Tahun 2024 - Maria Fransiska Meol; Nurul Syuhfal Ningsih; Nur Handayani (Indonesian Journal of Midwifery Scientific, 2025)
Background: Infant death can be caused by various factors, including if the baby's basic needs are not met, including eating, drinking and sleeping, which are one of the basic human needs, especially for babies because they are very beneficial for the health of each individual's body. Based on these problems, efforts are needed to increase the baby's weight and sleep quality. One way to overcome these problems is to use baby massage stimulation. Objective: To determine the effect of baby massage therapy on increasing weight and sleep quality in babies aged 6 - 12 months at TPMB Ika Natalia in 2024. Methodology: This research uses experimental research. This research is quantitative research where the research plan used is a quasi-experimental plan, with a pretest and posttest design with a control group. Results: for body weight, the results of the statistical tests carried out showed a significant value of 0.027 < 0.05, while for measuring sleep quality, the results of the statistical tests carried out showed a significant value of 0.000 < 0.05. Conclusions and Suggestions: There is an effect of baby massage therapy on increasing body weight and sleep quality in babies aged 6 - 12 months at TPMB Ika Natalia in 2024 and it is hoped that this research can be used as a source of information that there are "evidence based" results regarding one of the midwifery interventions which can be used to increase baby's weight and sleep quality through massage techniques.